Analisis Fundamental Makro, Struktur Kepemilikan Terhadap Nilai Perusahaan dengan Karakteristik Perusahaan, Kinerja Keuangan Sebagai Variabel Intervaning dalam Perusahaan Sektor Manufaktur yang Terdaftar pada Bursa Efek Indonesia pada Tahun 2019-2023 - Aditya, Farhan; Hwihanus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to determine and analyze the influence of macro fundamental factors and ownership structure on company value, with financial performance and company characteristics as intervening variables. The macro fundamental factors studied include inflation, gross domestic income, interest rates and foreign exchange rates. The ownership structure is analyzed based on institutional, foreign, public, government and managerial ownership. Financial performance is measured through receivables turnover, ROA and ROE. Company characteristics include the number of board of directors, number of audit committees, company size, and company age. Company value is assessed through share price, Tobin's Q, and EPS. This research uses data from 6 companies listed on the IDX in the 2019-2023 period and analyzed using SmartPLS. The research results show that macro fundamentals have a significant effect on company value, ownership structure, company characteristics and financial performance. Ownership structure also has a significant influence on company value, company characteristics and financial performance. In addition, company characteristics have a significant effect on company value and financial performance, and financial performance has a significant effect on company value. This research provides important insights for companies and investors in understanding the factors that influence company value and investment decision making.